RESEARCH OF STRATEGY COPING BEHAVIOR AT NEUROTIC PATIENTS - Irina Valerievna Belasheva; Alla Valentinovna Suvorova; Ella Michailovna Kozlova; Marine Levonovna Esayan (Вестник Северо-Кавказского федерального университета, 2022)
A brief abstract. Investigation of the structure of personality (neurotic personality traits) and coping behavior in patients with panic disorder and agoraphobia demonstrates the use of less adaptive behavior mechanisms. In the neurotic personality development rational defenses give way to the primary mechanisms such as giperkompensatornoe high self-esteem, repression of painful experiences, and the secondary defense mechanisms - rationalization to justify its failure disease, illness care, are exempt from responsibility for decision making.